A qualitative study of overdose responses among Chicago IDUs - Bigg Dan; Carlberg Suzanne; Scott Gregory; Gann Donald S; Sherman Susan G; Heimer Robert (BMC, 2008)
Abstract Background Opioid overdose is a leading cause of death among injection drug users. Over half of injection drug users report at least one nonfatal overdose during their lifetime. Death from opioid overdose rarely occurs instantaneously, but rather over the course of one to three hours, allowing ample time for providing life-saving measures. In response to the prevalence of overdoses in the U.S., there are a growing number of overdose prevention and naloxone distribution programs targeting the injection drug using community. Methods We explored injection drug users' experiences with opioid overdose response, examining differences between overdose responses in which naloxone was and was not used. The current study is based upon qualitative interviews (N = 31) with clients of the Chicago Recovery Alliance needle exchange program who had witnessed an overdose in the past six months. The interviews explored participants' drug use history, personal overdose experiences, and details concerning their last witnessed overdose. Verbatim transcripts were coded and analyzed thematically to address major study questions. Results Participants were 81% were male, their median age was 38. They reported having injected a median of 10 years and having witnessed a median of six overdoses in their lifetime. All described overdoses were recognized and responded to quickly. None of the overdoses resulted in a fatality and naloxone was successfully administered in 58% of the last witnessed overdoses. Administering naloxone for the first time was characterized by trepidation, but this feeling dissipated as the naloxone quickly took effect. Emergency medical personnel were called in 10 of the 31 described overdoses, including four in which participants administered naloxone. The overwhelming majority of experiences with police and paramedics were positive Conclusion Overall, our small study found that the overdose prevention efforts build on extensive knowledge possessed by IDUs. Teaching IDUs how to use naloxone is an effective risk reduction strategy.